Time-of-day effects on objective and subjective short-term memory task performance. (2nd September 2021) - Ceglarek, Anna; Hubalewska-Mazgaj, Magdalena; Lewandowska, Koryna; Sikora-Wachowicz, Barbara; Marek, Tadeusz; Fafrowicz, Magdalena
ABSTRACT: The time-of-day along with the synchrony effect (better performance at optimal times of the day according to the chronotype) on the cognitive performance has been well established in previous research. This influence is mediated by both circadian and homeostatic processes consistent with the Borbély two-process model. This experiment focused on the objective and subjective performance of the visual short-term memory task requiring holistic processing. Sixty-five young, healthy participants including 40 females were divided into morning and evening types and performed a given task in two sessions – in the morning and in the evening. Type division was made according to the chronotype questionnaire and polymorphism of the PER3 clock gene. The task was a modified version of Deese–Roediger–McDermott paradigm adjusted to study short-term memory, in which visual, abstract stimuli were used. The analysis was based on an exploratory approach investigating the influence of circadian and individual (sex) factors on execution of memory task. Evening types were more accurate in the task compared to morning types, regardless of the part of the day. The time-of-day effect was revealed on objective measures (reaction times for hits and false alarms) and subjective effort put into the performance. The reaction times were slower in the morning unlike the effort that was greater in the evening. The time-of-day × sex interaction was observed in the case of subjective effort: men described the task as more demanding in the evening. The results could be explained by differences in hemispheric dominance depending on the time-of-day. The report provides new patterns of behavioral data analysis, investigating sex aspects and use of self-assessment scales of performance.